Lipidomic changes in the liver of beagle dogs associated with Toxocara canis infection - Li, Hao-Yu; Zou, Yang; Elsheikha, Hany M.; Xu, Yue; Cai, Lang; Xie, Shi-Chen; Zhu, Xing-Quan; Zheng, Wen-Bin (Frontiers in Cellular and Infection Microbiology, 2022)
A global lipidomic analysis using liquid chromatography–tandem mass spectrometry was performed on the liver of beagle dogs infected with Toxocara canis to profile hepatic lipid species at 12 h post-infection (hpi), 24 hpi, and 36 days post-infection (dpi). This analysis identified six categories and 42 subclasses of lipids, including 173, 64, and 116 differentially abundant lipid species at 12 hpi, 24 hpi, and 36 dpi, respectively. Many of the identified lysophospholipids, such as lysophosphatidylglycerol, lysophosphatidylserine, and lysophosphatidylcholine, may contribute to the migration and development of T. canis during the early infection stage. Pathway analysis revealed significant alterations of several immune-inflammatory pathways, such as the B-cell receptor signaling pathway, the NF-kappa B signaling pathway, and the C-type lectin receptor signaling pathway at 12 and 24 hpi. These findings demonstrate the value of lipidomic profiling in revealing the extent of changes in the composition and abundance of hepatic lipidome caused by T. canis infection and their relevance to the pathophysiology of toxocariasis in beagle dogs.